Chemical constituents from Alnus mandshurica (Callier) Hand.-Mazz. and their chemotaxonomic significance. (August 2021) - Wu, Nan; Jin, Chunmei; Piao, Yan; Yin, Xiongjie; Sun, Mingyue; Xu, Yan; An, Renbo; Jin, Lili; Zhang, Changhao
Abstract: A new phenol compound, (9 S )-9-hydroxy-9-[(2-hydroxyphenyl)methoxy]-nonanoic acid methyl ester (1 ) was isolated from the stem bark of Alnus mandshurica (Callier) Hand.-Mazz., along with eight known compounds (2 –9 ). The structure of compound 1 was determined by spectral analyses, including HR-ESI-MS, 1D and 2D NMR (COSY, HMQC and HMBC) experiments. All the isolated compounds were reported for first time from A . mandshurica . Furthermore, compounds 3 –9 were found in the family Betulaceae for the first time. Graphical abstract: Image 1 Highlights: Total nine compounds were isolated from the stem bark of Alnus mandshurica (Callier) Hand.-Mazz. A new phenol compound was isolated from the stem bark of A. mandshurica. All the isolated compounds were reported for first time from A. mandshurica. Compounds 3 –9 were found in the family Betulaceae for the first time.